1992
DOI: 10.1148/radiology.182.1.1727316
|View full text |Cite
|
Sign up to set email alerts
|

Primary tuberculosis in childhood: radiographic manifestations.

Abstract: The aim of the study was to review the radiologic features of primary tuberculosis in childhood and to determine whether differences in patterns of disease occur among age and ethnic groups. Chest radiographs of 191 children with pediatric primary tuberculosis were reviewed by two observers. Lymphadenopathy, present in 92% of cases, was the most common abnormality identified on the initial chest radiograph and typically involved the hilar and paratracheal regions. Parenchymal abnormalities, identified in 70% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
0
12

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(136 citation statements)
references
References 0 publications
7
117
0
12
Order By: Relevance
“…In current study the sensitivity of thoracic CT scan and digital chest X-ray were 78.9% and 63.2%, respectively, which at least in part can be due to the digital and not conventional technique of chest Xray. In some studies, one of the most common abnormal patterns of chest X-ray in the affected children was consolidation and right hilar lymphadenopathy which is in accordance with previous studies [18][19][20]. On the other hand, the most common abnormal findings compatible with pediatric TB diagnosis on CT were consolidation, mediastinal lymphadenopathy and nodular infiltration, the two latter of which are not detected optimally by chest X-ray both in the current and previous studies [10].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In current study the sensitivity of thoracic CT scan and digital chest X-ray were 78.9% and 63.2%, respectively, which at least in part can be due to the digital and not conventional technique of chest Xray. In some studies, one of the most common abnormal patterns of chest X-ray in the affected children was consolidation and right hilar lymphadenopathy which is in accordance with previous studies [18][19][20]. On the other hand, the most common abnormal findings compatible with pediatric TB diagnosis on CT were consolidation, mediastinal lymphadenopathy and nodular infiltration, the two latter of which are not detected optimally by chest X-ray both in the current and previous studies [10].…”
Section: Discussionsupporting
confidence: 86%
“…The most common radiological features of childhood tuberculosis are lymphadenopathy (90% -95%) [8,9], consolidation (70%) [9,10] and pleural effusion [10] in primary tuberculosis and consolidation, nodular infiltration (25%) and cavity (20% -45%) in reactivation tuberculosis [11,12]. Many studies have demonstrated the superiority of thoracic CT scan over the conventional chest X-ray in early evaluation and long term management of children suspected to be infected by tuberculosis but there are only few studies focused on the role of digital chest X-ray in approach and management of childhood tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Parenchymal abnormalities are more common in older children than in infants and are usually combined with lymphadenopathy (2). The primary parenchymal focus is often seen in the middle or lower lobes or in anterior segments of the upper lobes (Fig.…”
Section: Primary Pulmonarytuberculosismentioning
confidence: 99%
“…Estas adenopatías usualmente son unilaterales y se localizan en las cadenas paratraqueales y en hilios pulmonares en la forma primaria de la infección (166). Las adenopatías sólo afectan al 5-10% de los pacientes con tuberculosis posprimaria (163).…”
Section: Hallazgos Mediastínicosunclassified
“…Aunque las adenopatías hiliares suelen ser habituales en la forma primaria de tuberculosis (166), nuestro estudio no ha conseguido demostrar diferencias significativas en cuanto al porcentaje de pacientes con agrandamiento hiliar entre los grupos cultivo positivo o negativo para M. tuberculosis.…”
Section:  Agrandamiento Hiliarunclassified